Indonesia Economic Quarterly, July 2015 : Slower Gains - World Bank (Washington, DC, 2015)
Midway through 2015, Indonesia remains confronted with an uncertain external environment, and domestic economic policy challenges have intensified. GDP decelerated to below 5 percent in the first quarter and private consumption expenditure, Indonesia’s engine of growth in recent years, is also slowing. Weaker growth has resulted in slower job creation, with recent employment rising only just enough to absorb the increase in working age population. While the commodity downturn since 2012 and policy response have affected output growth the most in resource-rich provinces, employment creation has come under pressure across Indonesia. Yet the scope for policy stimulus is limited and monetary policy in particular is constrained due to sticky inflation and persistent external vulnerabilities.